Design guidelines for MPC‐based frequency regulation for islanded microgrids with storage, voltage, and ramping constraints. Issue 8 (25th May 2017) - Liang, Liang; Hou, Yunhe; Hill, David John
Abstract : This study addresses the frequency regulation for a microgrid under islanded mode with variable renewables. Due to the structure and parameters of microgrids, the frequency of the system and the voltages on the buses are coupled. Furthermore, to smooth out the fast fluctuations of renewables, the controllability of components are quantified accurately. In this study, some critical and realistic considerations are identified and modelled, and the guidelines for battery energy storage system (BESS) sizing are thus obtained. First, the frequency and voltage regulation loops are coordinated by a non‐linear model predictive control (MPC) controller, and the controllable resources are sequentially dispatched. Second, the dynamic model for evaluating the state of charge (SOC) of BESS under a fast response is introduced. Finally, general guidelines of the required energy capacity of BESS and the length of MPC control horizons are quantified by deriving the process of the responding disturbances. Ramping rates and response time delays of controllable resources are involved in the mathematical analysis. The simulation results show that the effectiveness of the proposed MPC controller and design guidelines can be generalised for microgrids in islanded mode with two kinds of controllable operating resources, which are represented by diesel generators and BESS.